IMPLEMENTASI KEBIJAKAN DANA DESA DI KABUPATEN SEMARANG (STUDI KASUS DI DESA RANDUGUNTING, KECAMATAN BERGAS) - R., Tri Asmoro Wisnu; Santoso, R. Slamet (Journal of Public Policy and Management Review, 2018)
The village funds are funds sourced from the National Budget that allocated for the village, transferred through the District / City Regional Government Budget then proceeded to village budget. This policy is regulated in Government Regulation No. 60 of 2014 on Village Funds as amended in Government Regulation No. 8 of 2016. The village funds are used to finance the administration, village development and community empowerment. The nominal amount of village funds raises concerns in the implementation. Central Java is included in the province's largest recipient of village funds in Indonesia, District Semarang receives a significant increase in village revenue every year. In accordance with the recommendations of Semarang district government and initial observations, Randugunting village is a village that needs attention in the implementation of village fund policy. This study aimed to determine the implementation of policies and obstacles that are experienced in the implementation. This research uses descriptive qualitative method. The results showed that the implementation of village fund policy when it viewed from the stage of distribution, stage of use, and the reporting stage based of Bupati Regulation No. 71 of 2016 not maximized. The implementation of the village fund policy encountered obstacles, that is policy content and policy context. Researchers recommend to Randugunting Village Government to improve understanding of policy objectives, interests, strategies and responsiveness. Then the government needs to improve training and coaching, evaluate the process of setting policy implementers, and make adjustments to existing regulations.